IMPLEMENTASI SIX SIGMA DENGAN PENDEKATAN POKA YOKE GUNA REDUKSI BAGIAN CASE PACKER PADA PT. X - Ulum, Roudlotul; Munir, Misbach (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
X is one of the companies engaged in the manufacturing industry that produces cigarettes with the type of Machine-made Clove Cigarettes (SKM), or commonly known as clove cigarettes. known at the time of the packaging process (packaging) there are often problems that cause the appearance of the resulting product is not good. In order to achieve this condition continuous improvement must be made. To avoid high defects in the packaging process, one of the ways to do this is to apply six sigma with a poka yoke approach, starting from identifying problems or defects, improving steps, and establishing standards to maintain these qualities, which aim to achieve product quality which can meet the desired specifications of the company. Based on the results of the analysis conducted a comparison of the results of the number of defects before and after experiencing improvement based on the percentage of the average number of defects from 0,00066342% to 5.70032% so that after improvements have increased 5.7%.